Bridging the gap: Workflow analysis evaluating "work-as-imagined" versus "work-as-done" for cardiac risk calculation. (November 2019) - Schubel, Laura; Stein, Lucy; Barrientos, Ronald Romero; Valdiviezo, Carolina; Townsend, Mark; Basch, Peter; Weintraub, William; Hettinger, Zach; Laccay, Christine; Chaney, Kevin; Miller, Kristen
In a complex, dynamic system such as healthcare delivery, there is often a "gap" between work as imagined (how clinical workflow ideally occurs) and work as done (how clinical workflow occurs in real-time). Therefore, it is critical when implementing new health information technology to work within the constraints of hospital-specific workflow to understand the reality of work, rather than relying solely on how it is reported. The present research seeks to fully understand the current state of workflow as it relates to cardiovascular risk calculation, with the ultimate goal of implementing an atherosclerotic cardiovascular disease risk calculator within the clinicians' electronic health record. By conducting both interviews and observations, researchers were able to compare work as imagined to work as done in order to implement the risk calculator to meet clinician needs.